Agama, Modernisme, dan Kepengaturan: Agama Lokal Pasca-1965 - Karunia Haganta; Firas Arrasy (LP2M UIN Sunan Kalijaga, 2021)
This article aims to examine the relationship between the state and local religions which underwent major changes after the September 30, 1965 Movement. Local religions experienced marginalization after the 1965 tragedy, ranging from the stigma of atheism to not being recognized as a religion, but a culture that needs to be fostered and even prevented become a new religion. We analyze local state-religion relations from the perspective of James C. Scott's high-modernism and Michel Foucault's governmentality. In our analysis, the state plays a role in this process of marginalization by reproducing a modernity vision that is full of simplification of the complexity of local religions. Through various policies, the state carries out regulations that aim to change adherents of local religions to being good citizens according to the standards set by the state. The recognition given to local religions is very limited and even shows other discriminatory characteristics of the state such as determining monotheism as the standard of a religion, a criterion that is highly biased in the paradigm of world religions. We conclude that the state is not a solution because of the nature of modernity and the simplification it always contains.[Artikel ini bertujuan untuk mengamati relasi antara negara dengan agama lokal yang mengalami perubahan besar setelah terjadinya Gerakan 30 September 1965. Agama lokal mengalami marginalisasi setelah tragedi 1965, mulai dari stigma ateisme sampai tidak diakui sebagai agama, melainkan suatu kebudayaan yang perlu dibina dan bahkan dicegah untuk menjadi agama baru. Kami menganalisis relasi negara-agama lokal melalui perspektif high-modernism James C. Scott dan kepengaturan (governmentality) Michel Foucault. Dalam analisis kami, negara berperan dalam proses marginalisasi tersebut dengan mereproduksikan visi modernitas yang penuh simplifikasi terhadap kompleksitas agama lokal. Melalui berbagai kebijakan, negara melakukan kepengaturan yang bertujuan untuk mengubah penganut agama lokal menjadi subjek warga negara yang baik sesuai dengan standar yang telah ditetapkan negara. Pengakuan yang diberikan terhadap agama lokal amat terbatas dan bahkan menunjukkan sifat diskriminatif lain dari negara seperti menentukan monoteisme sebagai standar suatu agama, kriteria yang amat bias paradigma agama dunia. Kami menyimpulkan negara bukan solusi karena watak modernitas dan kepengaturan yang selalu dikandungnya.]